Feed the bees and shade the streams: riparian shrubs planted for restoration provide forage for native bees. Issue 3 (6th September 2021) - Mitchell, Scott R.; DeBano, Sandra J.; Rowland, Mary M.; Burrows, Skyler
Abstract : With evidence of pollinator declines and an increasing focus on restoration, interest is growing in investigating floral resources for native bees. Although native bees forage on shrubs, few studies have explored the pollinator communities of native shrubs and none have examined shrub‐pollinator interactions in riparian areas of the northwestern United States. Life history traits of shrubs may make them particularly important resources for bees, especially in early spring—a key point in the lifecycle of many bee species. We conducted extensive hand‐net surveys over 2 years in a large riparian restoration project in the Pacific Northwest to understand bee‐flowering plant interactions with the aim of guiding future restoration efforts. Although forb blooming stem abundance and richness were higher than that of shrubs in spring, 57% of bees observed foraging were on willow ( Salix spp.), a commonly planted riparian shrub. Season‐long, bee community composition on shrubs differed from that of forbs. Bee species diversity was highest on wax currant ( Ribes cereum ) and willow in early spring (April) and on black hawthorn ( Crataegus douglasii ) and mallow ninebark ( Physocarpus malvaceus ) later (i.e., June – July). Some bees showed a strong preference for wax currant and black hawthorn, both of which are more resistant to ungulate herbivory than other shrubs. Our results suggest that riparian restoration practitioners could consider using shrubs that provide forage to a diverse community of pollinators and improve stream health by shading and stabilizing banks. Planting bee‐friendly shrubs can help accomplish multiple restoration goals and leverage limited restoration funding.